ASSESSMENT OF MICROCLIMATE, FLOOR TYPE AND COLIFORM CONTAMINATION OF THE AIR IN INTENSIVE SHEEP UNIT - Yasotha, A; Sivakumar, T; Muralidharan , Ra (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
An experiment was conducted to assess and compare the coliform air pollution levels in slatted floor and mud floor of sheep pens. Weekly recordings were taken at 8 a.m. and 2 p.m for the estimation of coliform count in air and climatic variables viz. air temperature, relative humidity and air velocity. Coliform count was not statistically significant different between the floors even though the count was higher in mud floor (9.18 ± 3.20cfu per 30 l of air) than in slatted floor (5.25 ± 2.35 cfu per 30 l of air). The floor of sheep pens did not have any significant influence on the climatic variables but the period had a highly significant (P<0.01) influence on climatic variables.